The Effectiveness of Using Coffee Husk Trichocompost as a Nutrient Source to Increase the Yield of Large Red Chili Plants (Capsicum Annuum L.) - Nuraripa; Naima Haruna; Akmal (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Red chili (Capsicum annuum L.) is one of the important horticultural commodities in Indonesia that has high economic value and is widely used as a flavoring agent, food industry, and medicine. Red chilies also contain nutrients such as carbohydrates, fiber, phosphorus, and vitamins A, B, C, and K, which are beneficial to the human body. However, their productivity is still relatively low. One of the causes is the excessive use of inorganic fertilizers and cultivation without crop rotation which reduces soil fertility and increases attacks by plant pests so that efforts are needed to increase production through sustainable soil fertility management such as the use of coffee husk compost decomposed with Trichoderma decomposers to increase nutrient availability and improve the physical, chemical, and biological properties of the soil and suppress pathogen growth. This study aims to determine the effect and best dosage of the use of coffee husk compost with various doses of Trichoderma decomposers on the growth and productivity of large red chili plants. This study used a non-factorial Randomized Block Design (RBD) consisting of seven treatments of coffee husk trichocompost: K0 (control/soil), K1 (soil + 1.5 kg/bed of coffee husk compost without decomposer), K2 (soil + 1.5 kg/bed of coffee husk compost with the addition of 150 g of Trichoderma harzianum during composting), and K3 (soil + 1.5 kg/bed of coffee husk compost with the addition of 450 g of Trichoderma harzianum during composting).